2020
DOI: 10.1186/s13052-020-00852-1
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation, oxidative stress and risk of brain injury in preterm newborn

Abstract: Preterm infants have an increased risk of cognitive and behavioral deficits and cerebral palsy compared to term born babies. Especially before 32 weeks of gestation, infants may require respiratory support, but at the same time, ventilation is known to induce oxidative stress, increasing the risk of brain injury. Ventilation may cause brain damage through two pathways: localized cerebral inflammatory response and hemodynamic instability. During ventilation, the most important causes of pro-inflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Finally, when possible, noninvasive ventilation (NIV), such as nasal intermittent positive pressure ventilation (nIPPV) with the use of nasal continuous positive airway pressure (nCPAP), should be preferred. The nCPAP can be used from the delivery room to support first spontaneous breaths, reducing the risk of supplemental oxygen and intubation and improving long-term respiratory outcome [91,92]. A simple and effective lung protection strategy is to keep the lung "open" or recruited by finding the optimal level of PEEP for each patient, typically between 5 and 9 cm H 2 O, to maintain lung expansion and prevent end-expiratory alveolar collapse [86].…”
Section: Oxidative Stress and Ventilation-induced Lung Injurymentioning
confidence: 99%
“…Finally, when possible, noninvasive ventilation (NIV), such as nasal intermittent positive pressure ventilation (nIPPV) with the use of nasal continuous positive airway pressure (nCPAP), should be preferred. The nCPAP can be used from the delivery room to support first spontaneous breaths, reducing the risk of supplemental oxygen and intubation and improving long-term respiratory outcome [91,92]. A simple and effective lung protection strategy is to keep the lung "open" or recruited by finding the optimal level of PEEP for each patient, typically between 5 and 9 cm H 2 O, to maintain lung expansion and prevent end-expiratory alveolar collapse [86].…”
Section: Oxidative Stress and Ventilation-induced Lung Injurymentioning
confidence: 99%
“…The role of brain inflammation has been taken into account in the molecular cascade sustaining epileptic status in older children and adults [ 10 , 11 ]; however, it has been less defined in newborns with NSE related to different etiologies [ 5 , 12 , 13 , 14 ]. Indeed, the influence of oxidative stress as a risk factor for brain injury in newborns is well known, especially in preterm infants where there is an imbalance deriving from the overproduction of free radicals and the insufficient levels of antioxidant enzymes [ 15 , 16 ]. In particular, inefficient endogenous anti-inflammatory control of brain inflammation has been described both during chronic recurrent seizures and in SE, and in turn, prolonged inflammation has been suggested to sustain epileptic activity in neurons [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…56 In addition to the intubation procedure, mechanical ventilation is also a stressful and painful event that promotes the production of proinflammatory cytokines with long-term effects on the newborn's brain and behavioral development. 57 The premedication with sedatives, analgesics, and muscle relaxants has long been a consolidated practice in adults and children, but the role of continuous analgesia or sedation in preterm infants is controversial. However, to date, premedication prior to endotracheal intubation is recommended in neonates, because studies on both premature and full-term infants showed that it makes it easier for the intubation procedure and limits pain, stress, and worsening of vital signs.…”
Section: El Aton I N a Dm I N I St R At Ion Du R I Ng M Ec H A N Ica ...mentioning
confidence: 99%